STUDENTS LOAN AND ACCESS TO TERTIARY EDUCATION IN NIGERIA: IMPLICATION FOR EDUCATIONAL ADMINISTRATION AND PLANNING - Chinelo, Nwankwo Nkechi; Udegbe, Chigozie Charles; Oranusi, Ndidi Stella; Awadiegwu, Amaka Emmanuela (Journal of Social Science, 2026)
Objective: This study aims to explore the impact of the Students Loan Act on access to tertiary education in Nigeria, focusing on its implications for educational administration and planning. Method: The research employs quantitative methods to analyze data gathered from government reports, academic articles, and surveys. Results: The findings reveal that the implementation of the student loan program has significantly increased access to tertiary education, reduced financial barriers, and promoted equal opportunity and inclusiveness. Furthermore, it has contributed to human capital development, encouraged social mobility, and supported government educational policies. Novelty: This paper provides a comprehensive examination of the student loan system's role in addressing socio-economic inequalities and its positive effects on educational outcomes in Nigeria's tertiary institutions, highlighting its contributions to sustainable educational development and social equity